Simulation of the capacity and precision of working memory in the hypodopaminergic state: Relevance to schizophrenia. (4th June 2015) - Okimura, T.; Tanaka, S.; Maeda, T.; Kato, M.; Mimura, M.
Highlights: We performed a simulation of working memory (WM) impairments in schizophrenia. Hypodopaminergic modulation via D1 receptors caused reduced WM capacity. Hypodopaminergic modulation via D1 receptors caused WM imprecision. Enhancing NMDA receptor function improved these WM impairments. Abstract: Working memory (WM) impairment has received attention as a behavioral characteristic of schizophrenia. Neurobiological studies have led to the hypothesis that a deficit in dopamine transmission through D1 receptors in the prefrontal cortex (PFC) is associated with WM impairment in schizophrenia. However, empirical approaches that aim to clarify the nature of the impairment and its underlying mechanism are difficult to enact, especially in unmedicated patients. By contrast, computational approaches using biologically plausible models have formed a powerful theoretical framework for the study of WM impairment in schizophrenia. This article attempts to directly connect neurobiological findings to the neuropsychological behaviors present in patients with schizophrenia. Using a biologically plausible prefrontal cortical circuit model, we simulated sustained activity during a simultaneous, multi-target WM task. We subsequently analyzed how dopaminergic modulation via D1 receptor activation alters the capacity and precision of WM and investigated the underlying mechanism. Hypodopaminergic modulation resulted in imprecision and a reduced capacity in WM primarily due to decreased N -methyl-d -aspartate (NMDA) conductance. Increasing NMDA conductance ameliorated both impairments. These results account for the mechanism that underlies WM impairments in schizophrenia and provide a theoretical basis for combination therapy with antipsychotic drugs and drugs that enhance NMDA receptor function, which is expected to be effective for the treatment of WM impairments in these patients.